(untitled) (Research, Society and Development, 2023)
The present study aims to carry out a bibliographical review that highlights what the literature provides about the use of Scopolamine Butylbromide to control hypersecretion in patients undergoing palliative care, which is an effective and low-cost alternative. This is an integrative review carried out through Evidence-Based Research with the guiding question: “Has the use of Scopolamine to control hypersecretion been an alternative used to treat patients in palliative care? “. Using the descriptors: “Liquids and Secretions, “Scopolamine” and “Palliative Care at the End of Life” to search for studies. The application of search strategies on the selected platforms resulted in a filtered sample of 09 publications, which made up this review process. The largest number of publications on the topic were found in the Medical Literature Analysis and Retrieval System Online – MEDLINE database through PUBMED, with a total of 5 of the 9 research studies predominantly using English as the language. Through this literature review, it was possible to see that scopolamine can be used to control hypersecretion in patients receiving palliative care. The studies reinforced that in patients in the final stage of life it is common to increase the production of secretions, closely associated with their diagnosis. Non-pharmacological measures can improve this symptom. Scopolamine, as well as other anticholinergic drugs, has been shown to be effective for the treatment of hypersecretion.